Ultra-high energy storage in lead-free NaNbO3-based relaxor ceramics with directional slush-like polar structures design - Zhentao Wang; Da Li; Wenyuan Liu; Liqiang He; Diming Xu; Jinnan Liu; Jiajia Ren; Xin Wang; Yang Liu; Guoqiang He; Jian Bao; Zhen Fang; et al. (Nature Communications)
Abstract Multilayer ceramic capacitors with ultra-high-power densities are widely used in electronic power systems. However, achieving a balance between high energy density and efficiency remains a substantial challenge that limits the practical application of advanced technologies. Here, guided by a phase-field simulation method, we propose a directional slush-like polar structure design with nanodomains embedded in polar orthorhombic matrix in NaNbO3-based lead-free multilayer ceramic capacitors. This strategy can effectively reduce the hysteresis loss by lowering domain size and improve the breakdown electric field by grain refining, which leads to a high energy storage density of 14.1 J▪cm−3 and an ultrahigh energy storage efficiency of 96.8% in multilayer ceramic capacitors. The proposed strategy can be utilized to design high-performance energy storage dielectrics and other related functionalities.